Some factors related to lipid profile in obese children at junior high schools in Manado - Anneke Helena Tangkilisan; Kartin Akune (Indonesian Pediatric Society, 2007)
Background Factors related to lipid profile in obese children arecalorie intake, fast food consuming habit, gender, physical activity,television (TV) watching, sleep duration, and visceral fat distribution.Objective To determine factors related to lipid profile in obesechildren at junior high school.Methods We studied obese children aged 11-<15 years fromNovember 2004 to February 2005 at junior high school in Manadocity. One hundred and seven junior high school children aged 11-<15years were enrolled in this study, excluding children with acute disease,having hypothyroidism, diabetes mellitus, chronic renal disease, liverdisease, and using corticosteroid. The rsik factors considered werecalorie intake, fast food consuming habit, gender, physical activity, TVwatching, sleep duration, and waist circumference. The outcomemeasures were total cholesterol, LDL, HDL, non-HDL cholesterol,and triglyceride. Data was analyzed using X 2 , fisher exact test, Spearman’srho and multiple linear regression analysis with stepwise procedure.Results The prevalence of increased total cholesterol was 28%,LDL 44%, triglyceride 16.8%, low HDL cholesterol 6.5%, and non-HDL was 23.3%. There were statistically significant relationshipbetween gender, calorie intake, fast food consuming habit, physicalactivity, TV watching, sleep duration, and total cholesterol. Therewere also statistically significant relationship between calorie intake,habit of consuming fast food, physical activity, TV watching, sleepduration, and LDL cholesterol. Fast food consuming habit and TVwatching also had statistically significant relationship with HDLcholesterol. There were statistically significant relationship betweencalorie intake, physical activity, TV watching, and sleep durationwith non-HDL cholesterol.Conclusion Duration of TV watching, sleep duration, less physicalactivity and waist circumference >98 percentile are correlatedwith hyperlipidemia in obese children.